Column specific fixation for complex tibial plateau fractures – Midterm prospective study in South - Indian population. Issue 2 (February 2020) - Selvaraj, V.; Devadoss, Sathish; Jayakumar, S.; Gururagavendra, P.; Devadoss, A.
Highlights: Computed tomography(CT scan) is mandatory for tibial plateau fractures. Classify all the tibial plateau fractures according to three column classification system. Column specific internal fixation really helps in achieving better functional and radiological outcomes. Abstract: Background: Tibial plateau fractures involving two or more columns were routinely assessed by two-dimensional radiography in the past. This often misled surgeons and attention was given only to the medial and lateral column without consideration of the posterior column, especially the postero-medial corner. Luo in 2010 introduced the new three-column classification system based on multiplanar computed tomography images. This study was conducted to assess the outcome after internal fixation of tibial plateau fractures involving two or more columns in our centre based on the column specific approach. Materials and Methods: This was a prospective study conducted at our institute, between 2011 and 2016. Total of 183 patients with tibial plateau fractures involving two or more columns were admitted during this study period of which 123 patients were satisfied our inclusion criteria. 8 patients were lost to follow up. Hence 115 patients with tibial plateau fractures involving two or more columns were classified based on the new three column classification system. Dual column fixation (Anterolateral +Anteromedial) was done in 76 patients, (Anterolateral+Posteromedial) fixation in 25 patients and triple column fixation (Anterolateral + Anteromedial + Posteromedial) in 14 patients. Post operatively patients were assessed by Modified Rasmussen functional and radiological scoring system. Results: Based on Modified Rasmussen functional scoring system, 73 patients (63.5%) had excellent results, 37 patients (32.2%) had good results and 5 patients (4.3%) had fair results. Based on Modified Rasmussen radiological scoring system, 71 patients (61.7%) had excellent results, 38 patients (33.1%) had good results, 6 patients (5.2%) had fair results. 3 patients had deep infections. Conclusion: Based on our study, we like to conclude that we had good outcomes utilizing this modern column specific approach to the treatment of these two or more column tibial plateau fracture injuries, which includes assessment of three columns.